SIFAT MEKANIS BETON DENGAN SUBSTITUSI PARSIAL SERBUK BATU BATA PADA SEMENPORTLAND - Suparta, I Made; Karyawan Salain, I Made Alit; Wiryasa, Ngakan Made Anom (JURNAL SPEKTRAN; Vol 6 No 1 (2018): Vol. 6, No. 1, Januari 2018, 2018)
Waste bricks powder is pozzolan a material which contain silica and alumina activated that could react with the Portland cement (SPI). Compounds content SiO 2 + Al 2 O 3 + Fe 2 O 3 bricks powders from Desa Oebelo of 91%. The pozzolan materials pass quality specifications according to ASTM C618 where the amount of compounds SiO 2 + Al 2 O 3 + Fe 2 O 3 at least 70%. This research is to use of waste brick powder as a pozzolan material in concrete mixtures. Research on the mechanical properties of concrete with brick powder (SBB) as a partial substitution on the Portland cement (SPI) has been realized using cylindrical specimens of diameter = 150 mm and height = 300mm. The specimens were made by using a proportion, by weight, of 1.0 binder: 2.0 sand: 3.0 crushed stone and water binder ratio of 0.5. The binder was made by a mixture of SPI and SBB. The percentage of SBB in the binder varied: 0%, 10%, 20% and 30% by total weight of the binder. Thegrain distribution of sand and crushed stone were designed according to SNI 03-2834-2000 to meet respectively the gradation zone 2 for fine aggregate and the granules with a maximum diameter of 20 mm for coarse aggregate. The test of concrete mechanical properties included compressive strength, modulus of elasticity and split tensile strength and realized atthe specimen’s age of 28, 56, and 90 days respectively using three specimens for each test.The test result shows that the positive reaction of brick powderas a pozzolanic material can only be noted after the hydration age of 90 days. The development of compressive strength, modulus of elasticity and split tensile strength depend on the percentage of SBB used in the binder. In fact, the use of 10%SBB in the binder produce compressive strength, modulus of elasticity and split tensile strength respectively about 97%, 94%, and 98% compared to those produced using 100% SPI. This interesting performance could be strongly related to the pozzolanic effect of SBB on the long term of hydration. Keyword: brick powder, compressive strength, modulus of elasticity, split tensile strength